2000
DOI: 10.1034/j.1399-3003.2000.15e05.x
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide, serum ECP and airway responsiveness in mild asthmatic children

Abstract: The purpose of the present study was to assess the possible relationships between exhaled nitric oxide (ENO), a circulating marker of eosinophil activation, serum eosinophil cationic protein (SECP), level of airway responsiveness to methacholine and lung function in asthmatic children, as well as to compare these markers between children with and without inhaled steroid therapy.In a cross-sectional study ENO, SECP and bronchial hyperresponsiveness to methacholine were evaluated in a group of 57 asthmatic child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
(20 reference statements)
1
22
1
Order By: Relevance
“…Spacial differences within the lungs are not likely to be responsible for the divergence between eNO and lung function. It has been proposed that FEV1 may reflect the more central airways and that eNO may sample the more distal air spaces [22]. However, the authors did not find a concordance with MMEF (table 1) or the maximum expiratory flow at 25% vital capacity (data not shown).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Spacial differences within the lungs are not likely to be responsible for the divergence between eNO and lung function. It has been proposed that FEV1 may reflect the more central airways and that eNO may sample the more distal air spaces [22]. However, the authors did not find a concordance with MMEF (table 1) or the maximum expiratory flow at 25% vital capacity (data not shown).…”
Section: Discussioncontrasting
confidence: 47%
“…Various studies have, so far, investigated lung function and eNO in asthmatic children [20][21][22][23][24][25][26]. In a prospective, open, nonrandomized study the authors recently showed a lack of correlation between eNO and disease severity and only a weak prediction of the physician-recommended inhaled therapy by eNO in children with allergic asthma [14].…”
Section: Discussionmentioning
confidence: 99%
“…In children with asthma FE NO has been found to correlate with sputum eosinophilia 9 as well as eosinophilia in biopsy specimens, 22 and it is also associated with other clinical characteristics of asthma such as airway hyperresponsiveness, 23 bronchodilator responses, 24 and exercise induced bronchoconstriction. 25 In our patients FE NO was significantly associated with baseline lung function and with bronchodilator responses, although within the groups the correlations were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of F eno as an indicator of pulmonary infl ammation is relatively simple and inexpensive compared with other biomarkers, so there is great interest in the potential role for using F eno data in asthma management. F eno level has been shown to correlate with lung function, sputum eosinophil levels, and methacholine responsiveness, [9][10][11][12][13][14][15][16][17] and, therefore, may provide a noninvasive change of Ն 10 ppb for those with lower categories of infl ammation. We applied this algorithm, modifi ed for pediatric cut points (if F eno level increased by Ն 7 ppb for those with F eno values , 35 ppb or Ն 20% for those with F eno Ն 35 ppb) and found that a "significant" change in F eno level from the previous visit did not predict future health-care use ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…These are less likely given prior studies that demonstrate reproducibility of F eno measurements 34,35 and the strong, existing evidence of correlation between eosinophilic airway infl ammation and F eno level. 9,11,[13][14][15][16][17] There were limitations to the study design that warrant consideration. As our study population was limited to children in Baltimore City, results may not be generalizable to other populations.…”
Section: Role Of Sponsorsmentioning
confidence: 99%